1983
DOI: 10.2307/1590192
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Specific-Pathogen-Free Chicks to Concomitant Infections of Reovirus (WVU-2937) and Infectious Bursal Disease Virus

Abstract: Specific-pathogen-free white leghorn chicks concomitantly infected with both infectious bursal disease virus (IBDV) and reovirus (WVU-2937) on day 1 had significantly lower (P less than 0.05) virus-neutralizing- and precipitating-antibody geometric mean titers (GMT) to reovirus than chicks infected with only reovirus on day 1 but had a similar incidence of inflammation of the metatarsal digital flexor tendons. Chicks infected with IBDV on day 7 and reovirus on day 14 had a greater incidence of inflammation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 12 publications
1
6
1
Order By: Relevance
“…This also was seen in Tx + Cy birds but not in Tx birds. A similar effect of immunosuppression on the development of clinical tenosynovitis was observed in the study by Springer et al (1983) who found that when chicks pre-infected with IBDV were infected oronasally with reovirus they showed at 4 and 6 weeks a greater incidence of gross leg lesions and more severe microscopic lesions than in chicks not infected with IBDV. The greater severity of responses in infected Cy-treated birds in the present study, including mortality, may be attributed to the more severe immunosuppression of Cy compared to IBDV or to the relative virulence of the strains of reovirus used.…”
Section: Virus Isolationsupporting
confidence: 78%
See 3 more Smart Citations
“…This also was seen in Tx + Cy birds but not in Tx birds. A similar effect of immunosuppression on the development of clinical tenosynovitis was observed in the study by Springer et al (1983) who found that when chicks pre-infected with IBDV were infected oronasally with reovirus they showed at 4 and 6 weeks a greater incidence of gross leg lesions and more severe microscopic lesions than in chicks not infected with IBDV. The greater severity of responses in infected Cy-treated birds in the present study, including mortality, may be attributed to the more severe immunosuppression of Cy compared to IBDV or to the relative virulence of the strains of reovirus used.…”
Section: Virus Isolationsupporting
confidence: 78%
“…The greater severity of responses in infected Cy-treated birds in the present study, including mortality, may be attributed to the more severe immunosuppression of Cy compared to IBDV or to the relative virulence of the strains of reovirus used. The IBDV infection caused lower reovirus neutralising and precipitating antibody titres (Springer et al, 1983) while the Cy-treatment in the present study resulted in a complete failure to produce both types of antibody to reovirus.…”
Section: Virus Isolationcontrasting
confidence: 46%
See 2 more Smart Citations
“…Avian reovirus types AR-1 (Fahey-Crawley strain), AR-2 (strain 24) and AR-3 (strain 59) were from American Type Culture Collection (Rockville, Maryland, USA). All viruses were passaged at least 4 times in chicken embryo liver (CELi) cell cultures prepared from SPF chicken embryos (SPAFAS Inc., Storrs, Conn., USA), as described by Springer et al (1983) and plaque purified twice. The viruses were later adapted for growth in African green monkey kidney (Vero) cell lines as previously described (Rekik et al, 1990).…”
Section: Virus Sourcementioning
confidence: 99%